TikTok Politics: Tit for Tat on the India–China Cyberspace Frontier - Mishra, Megha; Yan, Pu; Schroeder, Ralph (International Journal of Communication, 2022)
TikTok has enjoyed wide popularity in the Global South. But in the summer of 2020, a tit for tat altercation erupted over the use of the app in India against the backdrop of a border dispute between India and China. India banned TikTok, along with other Chinese mobile applications. This ban raised larger ongoing issues around user privacy, cybersecurity threats, and content regulation issues on social media platforms and telecommunications equipment around the world. In this paper we explore these issues and the wider debates on social media. To do so, we interviewed policymakers and academics as well as representatives from India’s technology industry. We also applied computational linguistic analysis on 6,388 Twitter posts about the ban by Indian users. The discourses on Twitter show intense nationalistic rhetoric and that Indian Twitter users were vocal in urging the government to ban TikTok. In-depth expert interviews suggested there were intense geopolitical conflicts behind the TikTok ban. We situate these findings with a broader analysis of the current geopolitics of social media platforms.